FRI0729-HPR Rheumatology advanced nurse practitioners treat to target person centered care: ireland's policy framework. (12th June 2018) - Minnock, P.; Ryan, A.-M.; ,
Abstract : Background: Advanced practice refers to a registered nurse, educated to master's degree level, with the expert knowledge base, complex decision-making skills and clinical competencies for expanded practice beyond that of the first level nurse. Advanced practice characteristics are shaped by the speciality, local context and/or country of practice. Countries, as well as specialty areas are at different stages in the development of legislation, scope of practice, roles, responsibilities, education and clinical preparation. Rheumatology nursing development continues apace internationally. Objectives: To bring rheumatology advanced nurse practitioners (ANPs) to the forefront in the delivery of quality person-centered care, working to enhance patient outcomes and reduce the personal and societal burden of rheumatic musculoskeletal diseases. Methods: The Irish Rheumatology Nursing Forum proposed a business case for the development of advanced nurse practitioner posts to implement, as a standardised approach to care nationally, the therapeutic strategy of treat to target for patients with inflammatory arthritis. This was endorsed by the Irish Society for Rheumatology and approved by the Rheumatology National Clinical Programme in 2015. Subsequently this proposal was chosen by the Chief Nursing Office as a demonstrator project for the Department of Health (DOH) draft policy to raise the critical mass of ANPs in healthcare delivery. Results: In late 2017, the DOH allocated 22 new ANP posts to rheumatology services countrywide, aligned to the national integrated care programme for the prevention and management of chronic disease. These 22 candidate ANPs are now completing advanced practice education at MSc level run by a consortium of Irish universities (University College Dublin, Cork, Galway, and Trinity College Dublin). Supervision of the requisite 500 clinical hours at advanced practice level is being provided by local consultant rheumatologist in partnership with the universities. Local teams of key service, nursing, medical, and academic personnel have been established across all centres to oversee project development; implementation; utilisation of robust evaluation criteria to capture clinical impact and cost-effectiveness. Initial evaluation will focus on key performance indicator's related to patient access such as i) ratio of new patients seen to ANPs, ii) new:return attendance ratio, iii) percentage of referrals seen within three months, iv) percentage of non-attended appointments. Intermediate-long-term evaluation will encompasses patient care and health care outcome through evaluation of all nursing interventions such as health assessments; medication prescribing and optimisation; patient education; health promotion; comorbidity screening; referral to other professionals; ordering of investigations; patient and staff satisfaction survey data. Quality of care will be evaluated guided by published quality care indicators. Patient outcome will be evaluated using appropriate nursing sensitive and validated disease activity scores and patient reported outcome measures. Real-time data collection using a specifically commissioned epr will ensure cANPs are supported by the appropriate technology to treat to target. Conclusions: ANP-led care underpinned by evidence based practice and guidelines, continues to grow as a model of care delivery in rheumatology. Disclosure of Interest: None declared